2021
DOI: 10.1016/j.tranon.2021.101162
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD47 expression by interferon-gamma in cancer cells

Abstract: Highlights IFN-γ up-regulated CD47 expression from transcriptional level. IFN-γ induced CD47 expression via JAK-STAT1-IRF1 pathway. The up-regulation of CD47 expression induced by IFN-γ was widespread among cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…In line with this, the upregulation of CD47 by the IFN-g/JAK1/STAT1 pathway was reported by Ye et al in NCI-H1975 and A549 cells. 36 Supporting the role of IFN-g-induced CD47 in tumor metastasis, several investigators had also reported that IFN-g and CD47 could promote metastasis. 9,[37][38][39] As IFN-g can also induce the expression of PD-L1 in tumor cells, 40 the coordinate induction of CD47 and PD-L1 by IFN-g may underlie the pro-tumorigenic role of IFN-g during antitumor immunotherapy.…”
Section: Discussionmentioning
confidence: 93%
“…In line with this, the upregulation of CD47 by the IFN-g/JAK1/STAT1 pathway was reported by Ye et al in NCI-H1975 and A549 cells. 36 Supporting the role of IFN-g-induced CD47 in tumor metastasis, several investigators had also reported that IFN-g and CD47 could promote metastasis. 9,[37][38][39] As IFN-g can also induce the expression of PD-L1 in tumor cells, 40 the coordinate induction of CD47 and PD-L1 by IFN-g may underlie the pro-tumorigenic role of IFN-g during antitumor immunotherapy.…”
Section: Discussionmentioning
confidence: 93%
“…The CC membranes coated on the surface of the NLC were well-retained. CD47 on CC membranes can bind to the corresponding receptors on macrophages to avoid being phagocytized by macrophages (Zhy et al, 2021 ). Further, CD44 is a specific protein involved in interactions between cells on the surface of CC membranes, and affects the tumorigenesis and metastasis of tumor cells (Thakur et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, induction of CD47 on tumor cells, a prominent "don't-eat-me" signal, by IFN-γ relied on the JAK1-STAT1-IRF1 axis, which prevented phagocytosis of stressed tumor cells by macrophages. This finding was observed in various tumor cells, suggesting this is a universal immunosuppressive mechanism engaged by IFN-γ [118]. Furthermore, IFNs, in particular IFN-γ, can impact cellular metabolism by inducing tryptophan 2,3-dioxygenase (TDO) or indoleamine 2,3-dioxygenase (IDO), which catabolizes essential amino acid tryptophan to kynurenine.…”
Section: The Ifn-jak-stat Axis In Ios (The Yin and Yang)mentioning
confidence: 93%